مسؤوليـــــة الموظـــــــف العــــــــام عن إفشــــاء الســر المهنــــي - طالبي, ديامنته; سليمان, رقيق; جنحاني, ليلى (University of Eloued جامعة الوادي, 2023)
واجب الالتزام بكتمان السر المهني من الالتزامات السلبية المترتبة على الموظف العام بمقتضى القانون الأساسي العام للوظيفة العمومية 06 - 03، فبحكم وظيفته قد يطلع على معلومات سرية تخص الإدارة والأفراد يلتزم بكتمانها وعدم إفشائها لأن في ذلك مساس بالمبادئ الأخلاقية و إحداث ضرر بالمصلحة العامة والمصلحة الخاصة ،ونظرا للأهمية البالغة لكتمان السر المهني و لخطورة إفشائه، وضع المشرع الجزائري قواعد لحمايته ،ليترتب على مخالف هذا الالتزام تسليط عقوبة متمثلة في العقوبة التأديبية، وقد تتعدى إلى العقوبة الجزائية ، مع منح الموظف جملة من الضمانات تحميه من تعسف الإدارة, إلا أنه يجوز استثناء إفشاء السر المهني حماية للمصلحة العامة بترخيص من القانون وحماية للمصلحة الخاصة برضا صاحب السر أو في حالة الضرورة.The obligation to keep the professional secret is one of the negative obligations incurred by the public employee under the General Basic Law of the Public Service 06-03. By virtue of his job, he may see confidential information pertaining to the administration and individuals, and he is obligated to keep it secret and not disclose it, because that would prejudice moral principles and cause harm to the public interest and the private interest. In view of the great importance of keeping professional secrets and the danger of disclosing it, the Algerian legislator set rules to protect it,The violator of this obligation shall result in the imposition of a penalty represented in the disciplinary punishment, and it may exceed the penal punishment, while granting the employee a number of guarantees that protect him from the arbitrariness of management, except that the disclosure of professional secret may be excluded in order to protect the public interest with a license from the law and protect the private interest with the consent of the owner of the secret or in case of necessity.
مذكرة ماستر
Keywords: السػضف العا ، الدخ السيشي، إفذاء الدخ السيشي، عقػبة.; public servant, professional secret, disclosure of professional secret, punishment.